Clinical progress and advanced research of red blood cells based drug delivery system. (December 2021) - Li, Yichen; Raza, Faisal; Liu, Yuhao; Wei, Yiqi; Rong, Ruonan; Zheng, Mengyuan; Yuan, Weien; Su, Jing; Qiu, Mingfeng; Li, Y.; Raza, F.; Liu, Y.; et al.
Abstract: Red blood cells (RBCs) are biocompatible carriers that can be employed to deliver different bioactive substances. In the past few decades, many strategies have been developed to encapsulate or attach drugs to RBCs. Osmotic-based encapsulation methods have been industrialized recently, and some encapsulated RBC formulations have reached the clinical stage for treating tumors and neurological diseases. Inspired by the intrinsic properties of intact RBCs, some advanced delivery strategies have also been proposed. These delivery systems combine RBCs with other novel systems to further exploit and expand the application of RBCs. This review summarizes the clinical progress of drugs encapsulated into intact RBCs, focusing on the loading and clinical trials. It also introduces the latest advanced research based on developing prospects and limitations of intact RBCs drug delivery system (DDS), hoping to provide a reference for related research fields and further application potential of intact RBCs based drug delivery system.